Peningkatan Kemampuan Mengenal Huruf Alfabet Dengan Media Ranting Pohon Pada Kelompok B TK Ash-Shidiq Bandung - Endah Jubaedah; Sopiyah Adawiyah (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2026)
One component of early childhood literacy language development is the ability to read the letters of the alphabet. It is very important for children to learn the letters of the alphabet as this serves as the foundation for reading and writing skills, which have a major impact on overall language development. This research began when initial observation research at Ash-Shidiq Kindergarten showed that the condition of the children in group B had not yet reached the expected level of success. Conventional literacy learning methods and ineffective use of media are the causes. The aim of this research was to determine the ability of group B of Kindergarten Ash-Shidiq to recognize the letters of the alphabet before and after the action using tree branches as a medium. This research uses a type of classroom action research (PTK), and the research subjects were ten children from group B. The research was conducted in two cycles based on the STPPA indicator for language literacy skills in recognizing letters of the alphabet. The data collection technique used is interviews, documentation, and observations. The results of research using tree twig media as a whole in improving the ability to recognize alphabet letters in group B at Ash-Shidiq Kindergarten can increase children's abilities optimally. This is shown by the percentage of children's success in each cycle, namely 20% in the pre-cycle, 60% in cycle I, and 90% in cycle II. Keywords: Early Childhood, Alphabet Letters, Tree Twig Media